2012
DOI: 10.1097/yct.0b013e31824b74f5
|View full text |Cite
|
Sign up to set email alerts
|

Rocuronium and Sugammadex Used Effectively for Electroconvulsive Therapy in a Patient With Brugada Syndrome

Abstract: We report the successful anesthetic management of a patient with Brugada syndrome who underwent electroconvulsive therapy to treat bipolar disorder. Suxamethonium and neostigmine were contraindicated to avoid the vagotonic effects that can precipitate ventricular fibrillation during anesthesia in patients with Brugada syndrome. The combination of 1.2 mg/kg rocuronium and 10 mg/kg sugammadex was effectively and safely used to induce and antagonize neuromuscular block for 8 consecutive electroconvulsive therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…Neostigmine did not cause any abnormalities in our case as well. Sugammadex could be effectively and safely used to antagonize neuromuscular block (10). Although the most common opioid used in patients with Brugada syndrome is fentanyl (11), Ahn and Kim (12) reported the successful use of remifentanil.…”
Section: Discussionmentioning
confidence: 99%
“…Neostigmine did not cause any abnormalities in our case as well. Sugammadex could be effectively and safely used to antagonize neuromuscular block (10). Although the most common opioid used in patients with Brugada syndrome is fentanyl (11), Ahn and Kim (12) reported the successful use of remifentanil.…”
Section: Discussionmentioning
confidence: 99%
“…were employed in the BS cases in this study. The intravenous anesthetic propofol was used for both the induction [27][28][29][30][31][32][33][34][35][36][37][38] and maintenance of anesthesia [29,[37][38][39][40] while midazolam was utilized for both premedication [31,34,37,38,41] and induction. [27,29,33] Only the one case in which ketamine and diazepam were used died, [42] and this was due to sedation with high-dose ketamine, which led to cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
“…However, concerns about neostigmine have led some authors to prefer sugammadex, which was used safely in two of the reported cases. [30,36] Additionally, we found that atropine was selected for use in only one case [54] and that glycopyrrolate [27,31,45,48] was more commonly applied as an anticholinergic agent.…”
Section: Dischargedmentioning
confidence: 99%
See 1 more Smart Citation
“…However, sugammadex is safe and effective in these patients. [39][40][41] Patients with liver disease have longer blockade recovery times, even after administration of neostigmine, due to slower hepatic metabolism of rocuronium or vecuronium. 42 The encapsulation by sugammadex alters the excretion of rocuronium or vecuronium to a liver-independent, renal pathway and allows safe administration in patients with hepatic dysfunction.…”
Section: Special Populationsmentioning
confidence: 99%